On Reciprocity and Practical Morality: A Response to Sagan and Valentino. Issue 4 (2019) - Walzer, Michael
Abstract: The findings reported in the article "Just War and Unjust Soldiers: American Public Opinion on the Moral Equality of Combatants, " by Scott Sagan and Benjamin Valentino, are indeed disturbing, but I am not convinced that they tell us all we need to know about public attitudes. Different questions, those that invite respondents to reflect on the reciprocal nature of practical morality (exemplified by the golden rule: "Do unto others . . ."), might reveal very different views of justified and unjustified conduct in war. I believe that these views, regarding, for example, the treatment of prisoners of war, would probably support the idea of the moral equality of soldiers on the battlefield.